Catholic semiotics in Shakespearean drama - Woods, GM (2006)
The preoccupation with the biographical question “Was Shakespeare a Catholic?” has obscured the literary significance of the residual Catholicism in his plays. Problematically representing England’s heritage and also its contemporary enemy, Catholicism has an awkward but unavoidable resonance when it appears in early modern drama. On the one hand polemic and (some) legislation produced a firm sectarian binary whereby superstitious, hypocritical and treacherous papists differentially defined a Protestant ideal. But on the other, English religious identity was a hybrid of traditional beliefs, non-theological nostalgia and political-religious disapprobation of Romish corruption. Attending to both flux and dichotomy, I demonstrate that looking at the way Catholic signs signify enriches our understanding of the texts of which they are a structural and structuring part. I consider a diversity of plays to show that just as Catholic resonance alters according to context, generic difference is also partly determined by ideological content. Catholicism was associated with ideological fraud and thus its literary presence renders the early modern concern about the moral and philosophical validity of fiction both more evident and more pressing. I explore what Shakespeare’s use of residual Catholicism tells us about his attitude to the value of creativity.